Donors use evidence to inform their investment strategies that guide and support nutrition-sensitive programming and policies in West Africa - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Recognizing the wide influence of Transform Nutrition, the Bill & Melinda Gates Foundation invested $4 million to launch the three-and-a-half-year Transform Nutrition West Africa initiative for nutrition knowledge generation and mobilization across the region